“Я ...заурядный учитель...” (зі спогадів І. Є. Маріковського) - Грибанова, О. (Архіви України, 2008)
Hrybanova O. provides description of an unpublished manuscript of I. Marikovs’kyi, a village teacher from the State Archives of Alma-Ata Oblast (Republic of Kazakhstan).